ANALISIS DETERMINAN PERILAKU PENCEGAHAN PENULARAN TUBERKULOSIS - Eny Sendra; John Davison Haluruk; Rolly Harvie Stevan Rondonuwu; Wirda Wirda (Ensiklopedia Research and Community Service Review, 2026)
Tuberculosis (TB) is an infectious disease that remains a global public health problem to this day. According to a report by the World Health Organization (WHO), tuberculosis ranks among the top ten causes of death worldwide and remains one of the infectious diseases requiring serious attention from various countries. The purpose of this study was to analyze the determinants of behavior related to the prevention of tuberculosis transmission. A cross-sectional study design was used in this research. The study was conducted in the service area of the Sumbersari Community Health Center (Puskesmas). The population consisted of all tuberculosis patients in the service area of the Sumbersari Community Health Center. The sample comprised 32 respondents. Total sampling was used as the sampling technique. A research questionnaire was used as the research instrument. Data analysis was performed using univariate and bivariate methods. The results indicate a relationship between knowledge (p-value: 0.020) and attitude (p-value: 0.000) and behaviors aimed at preventing the transmission of tuberculosis. It is recommended that community health centers provide comprehensive information and education to support the public’s level of knowledge and attitude regarding the prevention of pulmonary tuberculosis.Keywords: Knowledge, Attitudes, Tuberculosis